2014
DOI: 10.1002/j.1681-4835.2014.tb00464.x
|View full text |Cite
|
Sign up to set email alerts
|

Managing Gender‐Related Challenges in ICT4D Field Research

Abstract: A significant number of ICT4D projects funded by the developed world cannot meet their objectives. One cause of failures of ICT4D projects is likely to be the failures or shortcomings of the field research component since it is an integral part of a majority ICT4D projects. Hence, it becomes an imperative for researchers to be able to manage the challenges encountered in ICT4D field research. Project management principles (PMP) concerned with the scope, time, cost, quality, human resources, communications, and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 8 publications
(5 citation statements)
references
References 30 publications
0
5
0
Order By: Relevance
“…We followed the best practices prescribed in the literature (e.g., Potnis, 2014; Potnis & Gala, 2020) when engaging with vulnerable women. After receiving Institutional Review Board's approval from our academic institute, our study was announced to members by administrators with a link to the Qualtrics phone interview scheduling form, which requested members to enter two convenient time‐slots of at least 30 min on weekdays of their choice and contact information.…”
Section: Methodsmentioning
confidence: 99%
“…We followed the best practices prescribed in the literature (e.g., Potnis, 2014; Potnis & Gala, 2020) when engaging with vulnerable women. After receiving Institutional Review Board's approval from our academic institute, our study was announced to members by administrators with a link to the Qualtrics phone interview scheduling form, which requested members to enter two convenient time‐slots of at least 30 min on weekdays of their choice and contact information.…”
Section: Methodsmentioning
confidence: 99%
“…We followed the best practices prescribed in the literature (e.g. Potnis, 2014;Potnis and Gala, 2020) when engaging with vulnerable women. For instance, we retained the anonymity of study participants throughout the process.…”
Section: Methodsmentioning
confidence: 99%
“…Devendra Potnis, Chair, SIG‐III, and Bhakti Gala, Chair, South Asia Chapter presented and led the discussion on the nature of the lack of a conducive research environment in developing countries. Based on their research in developing countries (e.g., Potnis, 2014; Potnis, 2015; Potnis et al, 2017; Potnis & Gala, 2020a; Potnis & Gala, 2020b), the following challenges to conducting and publishing research in developing countries were identified and discussed. Lack of rigorous training for conducting research (e.g., lack of doctoral programs in developing countries) Lack of access to electronic resources such as EBSCO, dissertations, and journals, among others Lack of research culture (e.g., lack of awareness of research collaboration opportunities) Lack of institutional mechanisms (e.g., review boards) for approving research designs and methodologies Lack of organizational structure supporting researchers, including female researchers Lack of funding opportunities at the institutional, regional, and national levels Challenges related to planning research projects Challenges related to engaging with different types of populations for data collection Lack of expertise in data analysis techniques Lack of training for composing and publishing manuscripts Pit Pichappan, a member of SIG‐III, recommended adding a lack of mentorship to the list. Md.…”
Section: Background Of the Panelmentioning
confidence: 99%